Instrumental aspects of proportionality in civil proceedings - O. H. Bortnik; T. V. Stepanenko (Law and Safety)
The purpose of the work is to define the role of proportionality as a tool for overcoming legal uncertainty in the application by courts of the principles and norms of law in modern civil proceedings. It was supported the statement that within the limits of modern legal understanding, different from the objective or subjective determination of legal phenomena, which were traditionally characteristic of the national legal doctrine, the understanding of principles is not limited to the properties of technical means for constructing norms or means of overcoming gaps in legal regulation. The principles of law determine the purpose, possibility, regime and limits of law enforcement.